(untitled) - Kearey, Philip (Boston, 1996)
Contents: Historical perspective; Internal structure of the Earth; Continental drift; Sea floor spreading; The framework of plate tectonics; Ocean ridges; Transform and transcurrent faults...
Keywords: Plate tectonics,Tấm kiến tạo